2020
DOI: 10.1039/d0dt01730b
|View full text |Cite
|
Sign up to set email alerts
|

Loading and release of doxorubicin hydrochloride from iron(iii) trimesate MOF and zinc oxide nanoparticle composites

Abstract: The porosity of iron(iii) trimesate and the presence of nanoparticles significantly affect the loading and release of doxorubicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…It was reported that the prepared bio-nanocomposite could be used for anticancer drug delivery. Bhattacharjee et al [175] successfully incorporated ZnO into Fe (III) trimesate metal-organic framework (MIL-100(Fe)) to deliver anticancer drugs of doxorubicin hydrochloride (DOX) by the one-pot in-situ method. The investigation rendered interesting insights into the incorporation of NPs into MIL-100(Fe) and its drug loading capacity as well as release rates.…”
Section: The State-of-the-art Of Composites Containing Zn and Mg In Dmentioning
confidence: 99%
“…It was reported that the prepared bio-nanocomposite could be used for anticancer drug delivery. Bhattacharjee et al [175] successfully incorporated ZnO into Fe (III) trimesate metal-organic framework (MIL-100(Fe)) to deliver anticancer drugs of doxorubicin hydrochloride (DOX) by the one-pot in-situ method. The investigation rendered interesting insights into the incorporation of NPs into MIL-100(Fe) and its drug loading capacity as well as release rates.…”
Section: The State-of-the-art Of Composites Containing Zn and Mg In Dmentioning
confidence: 99%
“…Drug delivery systems that comprise metal–organic frameworks (MOFs) as carriers or vehicles have proven to be attractive over the years and several researchers have reported cases with a focus on drug loading and delivery. It is equally interesting to realize that MOFs are excellent platforms for a sustained and controlled release of drug molecules, and the property is potentially demanding for those drugs in the pharmaceutical industry that face major formulation-related problems of low water solubility, , thus leading to the decreased bioavailability of active pharmaceutical ingredients (APIs). It is not surprising that the focus has shifted to the latter with new investigations, if not too many, emerging on the sustained and controlled release of drugs from MOF-based drug delivery systems (DDSs). …”
Section: Introductionmentioning
confidence: 99%
“…MOFs are hybrid crystalline materials that consist of cationic metal nodes and anionic/neutral organic linkers connected via coordination bonds expanding in three dimensions. The high pore volume and surface area of MOFs have attracted researchers from all over the world, enabling their use in various applications, namely, gas storage, , catalysis, , dye adsorption, drug delivery, , etc. Many MOFs possess a variety of biological applications aided by (i) biocompatibility, biodegradability, and nontoxicity; (ii) facile surface chemistry that allows conjugation of various functionalities; (iii) the ability to load a variety of cargos; , (iv) stability within the gastrointestinal tract; etc .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported the use of MOFs in combination with chemotherapy drugs, doxorubicin, paclitaxel, etc., for the treatment of lung cancer, which proves the MOF-loaded drug system for doxorubicin and paclitaxel to be significantly effective. [20][21][22][23][24] Researchers are also trying to surface-modify MOFs in order to increase their absorption and drug-loading efficiency, improve the stability of MOFs' oral drug delivery systems, and regulate the compatibility between MOFs and biological systems. 25 Computer simulation technology refers to a technical method that dynamically simulates or re-enacts the UiO-66-NDC 0.7 400-500 14 behavior of a complex system on a digital computer so as to obtain quantitative indicators of the characteristics of the system and provide a basis for the decision-making process, 26 which is not limited by experimental conditions, time, and space and has great flexibility and arbitrariness.…”
mentioning
confidence: 99%